Hybrid green organic/inorganic filler polypropylene composites: Morphological study and mechanical performance investigations - Hayajneh Mohammed T. (De Gruyter, 2021)
In this study, the morphological and mechanical performances of hybrid green organic and inorganic filler composites were investigated. Various hybrid reinforcements using natural waste fillers including lemon leaves and eggshells were utilized for the study. The tensile strength, tensile modulus, elongation to break, flexural strength, and flexural modulus were investigated for the composites with polypropylene matrix. The results revealed that eggshells composites had the best values for both tensile and flexural tests while lemon leaves composites had the lowest values. However, the hybrid filler (lemon leaves-eggshells) had intermediate values. The poor properties of lemon leaves were attributed to the agglomeration and weak bonding presented by the morphological analysis of the hybrid composites.